Prevalence of occupational exposure to asthmagens derived from animals, fish and/or shellfish among Australian workers. - El-Zaemey, S.; Carey, R.; Darcey, E.; Reid, A.; Glass, D.; Benke, G.; Driscoll, T.; Peters, S.; Si, S.; Abramson, M.; Fritschi, Lin (2017)
Objective: Several animal, fish and/or shellfish derived substances encountered in the workplace can initiate or exacerbate asthma. The aims of this study were: to produce a population-based estimate of the current prevalence of occupational exposure to animal, fish and/or shellfish derived asthmagens, to identify the main circumstances of exposures and to identify occupations with the highest proportions of exposed respondents. Methods: We used data from the Australian Work Exposure Study-Asthma, a national telephone survey that investigated the current prevalence of occupational exposure to asthmagens among Australian workers. A web-based tool was used to collect job task information and assign exposure to asthmagens, including animal, fish and/or shellfish derived asthmagens. Prevalence ratios to determine risk factors for exposure were estimated using modified Poisson regression. Results: Of the 4878 respondents, 12.4% were exposed to asthmagens derived from animals, fish and/or shellfish. Exposure to these asthmagens was significantly higher in workers residing in regional and remote areas, compared with major cities. The main circumstance of exposure to animal derived asthmagens was through cleaning up rat/mice infestations, while the main circumstance of exposure to fish and/or shellfish derived asthmagens was through preparing and cooking salmon. Occupational groups with the highest proportion of exposure to animal or fish and/or shellfish derived asthmagens were farmers/animal workers and food workers, respectively. Conclusions: This is the first study investigating occupational exposure to animal, fish and/or shellfish derived asthmagens in a nationwide working population. The results of this study can be used to inform the direction of occupational interventions and policies to reduce work-related asthma.